Statistical Properties of Electron Curtain Precipitation Estimated With AeroCube‐6. Issue 12 (1st December 2020) - Shumko, M.; Johnson, A. T.; O'Brien, T. P.; Turner, D. L.; Greeley, A. D.; Sample, J. G.; Blake, J. B.; Blum, L. W.; Halford, A. J.
Abstract: Curtain precipitation is a recently discovered stationary, persistent, and latitudinally narrow electron precipitation phenomenon in low Earth orbit. Curtains are observed over consecutive passes of the dual AeroCube‐6 CubeSats while their in‐track lag varied from a fraction of a second to 65 s, with dosimeters that are sensitive to >35‐keV electrons. This study uses the AeroCube‐6 mission to quantify the statistical properties of 1, 634 curtains observed over 3 years. We found that many curtains are narrower than 10 km in the latitudinal direction with 90% narrower than 20 km. We examined the geographic, magnetic local time, and geomagnetic dependence of curtains. We found that curtains are observed in the late‐morning and premidnight magnetic local times, with a higher occurrence rate at premidnight, and curtains are observed more often during times of enhanced Auroral Electrojet. We found a few curtains in the bounce loss cone region above the North Atlantic, whose electrons were continuously scattered for at least 6 s. Such observations suggest that continuous curtain precipitation may be a significant loss of >35‐keV electrons from the magnetosphere into the atmosphere. We hypothesize that the curtains observed in the bounce loss cone were accelerated by parallel electric fields, and we show that this mechanism is consistent with the observations. Plain Language Summary: Electron curtain precipitation from space into Earth's atmosphere is a recently discovered phenomenon observed by dual‐spacecraft missions such as the AeroCube‐6 CubeSats that are nearly in the same orbit, ≈700 km above Earth's surface. Curtains appear stationary between consecutive passes of the AeroCube‐6 CubeSats, while the leader CubeSat was ahead of the follower CubeSat by up to a minute in orbital time. Curtains are also very narrow along the satellite orbit that is mostly in the latitudinal direction. Besides these two properties, curtains and their impact on the magnetosphere and atmosphere are not well understood. Therefore, we used the AeroCube‐6 mission that took data together for 3 years to statistically quantify curtain properties and to better understand their origin. We found 1, 634 curtains and found that 90% of curtains are narrower than 20 km in the latitudinal direction, curtains are observed on the outer radiation belt field lines predominately in the antisunward region, and curtains are observed when the magnetosphere is disturbed. Curtains observed in a special region above the North Atlantic shed light on their origin. A surprising result is that a few dozen curtains observed in this North Atlantic region were continuously precipitating into the atmosphere for multiple seconds. Therefore, curtains may be a significant source of atmospheric ionization responsible for the natural depletion of ozone. Key Points: The dual AeroCube‐6 CubeSats are used to identify stationary, narrow in latitude, and persistent >35‐keV electron curtain precipitation Ninety percent of the observed curtains in low Earth orbit are narrower than 20 km in the latitudinal direction Some curtains continuously precipitated into the atmosphere for multiple seconds